KERAGAMAN GENETIK BEBERAPA CABAI RAWIT (Capsicum frutescens L.) LOKAL ASAL SULAWESI TENGGARA - SUDIARSIH, TIRA; BOER, DIRVAMENA; HADINI, HAMIRUL; SUTARIATI, GUSTI AYU KADE; ANIMA HISEIN, WAODE SITI; WIJAYANTO, TEGUH (Jurnal Agroteknos, 2023)
This study aims to determine the genetic diversity of several local cayenne pepper cultivars from Southeast Sulawesi and to find out which local cayenne pepper cultivars from Southeast Sulawesi show the best growth and yields. This research was carried out at the Agricultural Extension Center (BPP) Pilot Land located in Langkoroni Village, Maligano District, Muna Regency. The research implementation time starts from October 2021 to February 2022. Data analysis using variety fingerprints, if it shows a real and very real influence then continued Duncan multiple range test (DMRT) with the help of statistical product and service solution (SPSS) application facility and calculate genetic diversity value. The results showed that quantitative characters with high diversity were found in the characters of flowering age, harvest age, number of fruits, fruit weight, fruit length and fruit diameter. Somewhat high is found in the character of plant height and leaf area. Slightly low was found in the character of the number of leaves and low was found in the character of the length of the fruit stalk. The qualitative characters observed were uniform because there were no differences in the observed local cayenne pepper cultivars from Southeast Sulawesi. The local cayenne pepper cultivar from Southeast Sulawesi that showed the highest growth and fruit yield was found in the cultivar from Kolaka (145.96 grams/plant), followed by North Buton-2 (125.71 grams/plant), then South Konawe (121.93 grams/plant) compared to other local cayenne pepper cultivars.